An Analysis of Students' Grammatical Errors in Writing Recount Text at Eleventh Grade of SMA Negeri 5 Prabumulih - Sri Hartati; Sri Yuliani; Lesi Lesi (Journal on Education, 2023)
This thesis is entitled "An Analysis of Students' Grammatical Errors in Writing Recount Text at Eleventh Grade of SMA Negeri 5 Prabumulih". Formulation of the problems: What is the most common Grammatical Error made by the Eleventh Grade Students of SMA Negeri 5 Prabumulih? The research objectives were to find out the most common grammatical errors made by the eleventh-grade students of SMA Negeri 5 Prabumulih. The population of this research was all the eleventh grade of SMA Negeri 5 Prabumulih in the academic year of 2020/2021, which consisted of five classes with a total population of 133 students. The sample of this study was 30 students taken using the purposive sampling technique. The researchers used a descriptive qualitative method. The data was collected through a writing test for students to make a recount text. The analysis finding showed that the total of student errors was 76. There were 31 omission errors (42, 46%), 22 addition errors (30, 13%), 15 misformation errors (20, 54%), and 8 misordering errors (10, 95%). The researchers conclude that the highest percentage of errors was omission errors, which were the dominant errors.